Visualizing and quantifying biomineral preservation in fossil vertebrate dental remains - Matthew B. Cowen; Marc de Rafélis; Loïc Ségalen; Benjamin P. Kear; Maïtena Dumont; Živilė Žigaitė (PeerJ)
In this study, we attempt to illustrate fossil vertebrate dental tissue geochemistry and, by inference, its extent of diagenetic alteration, using quantitative, semi-quantitative and optical tools to evaluate bioapatite preservation. We present visual comparisons of elemental compositions in fish and plesiosaur dental remains ranging in age from Silurian to Cretaceous, based on a combination of micro-scale optical cathodoluminescence (CL) observations (optical images and scanning electron microscope) with in-situ minor, trace and rare earth element (REE) compositions (EDS, maps and REE profiles), as a tool for assessing diagenetic processes and biomineral preservation during fossilization of vertebrate dental apatite. Tissue-selective REE values have been obtained using laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), indicating areas of potential REE enrichment, combined with cathodoluminescence (CL) analysis. Energy dispersive X-ray spectroscopy (EDS) mapping was also used to identify major elemental components and identify areas of contamination or diagenetic replacement. We conclude that the relative abilities of different dental tissues to resist alteration and proximity to the exposure surface largely determine the REE composition and, accordingly, the inferred quality of preserved bioapatite.